First Language Acquisition in Early Childhood at PAUD Melati Gan Sukabumi - Hidayah Supriyati; Surastina Surastina; Supriyono Supriyono; Galuh Dwi Ajeng (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2020)
This study aims to determine and examine the acquisition of first language in early childhood in PAUD Melati Gan. This research is a qualitative research using the analysis method, namely by analyzing the data in the form of phonology, phrases and sentences obtained from research respondents. Data collection was obtained from interviews, dialogues, observations, literature studies and data regarding the acquisition of the first language in PAUD Melati Gan. Based on the results of the study, it can be concluded that the acquisition of language of children aged 2 to 3 years was developed through several stages, namely (1) the stage of two-word speech, (2) the stage of inflection and agglutinative, and (3) the stage of the question and deny sentence patterns. The findings show that children's phonological acquisition is flawless around the age of 2-3 years, particularly the pronunciation of vowel sounds followed by consonant sounds. In these ages, children’s morphological aspect also increased. They grasp hundreds words during this periods.